The Influence of Entrepreneurial Orientation and Information Technology on the Performance of MSMEs - Nurul Qalbiah; Hikmahwati; Noor Safrina (Ilomata International Journal of Social Science, 2023)
MSMEs play an important role in the economic development of a country. Efforts are needed to improve the performance of MSMEs to ensure their continuity and continuity. Banjarmasin as the capital of South Kalimantan Province has experienced significant progress in developing MSMEs. However, many new businesses struggle to survive for various reasons. This indicates that the performance of MSMEs in Banjarmasin has not achieved satisfactory growth. This research aims to analyze the influence of entrepreneurial orientation and information technology on the performance of MSMEs in Banjarmasin. The research population consisted of MSME entrepreneurs registered with the Banjarmasin Cooperatives and Industry Service. This research uses a quantitative descriptive approach. The analytical method used is Multiple Linear Regression, Goodness of Fit Model testing, coefficient of determination (R-squared), and F test. The results of the research show that Entrepreneurial Orientation has a significant influence on the performance of MSMEs in Banjarmasin, with a significance value (Sig) of 0.021. Information Technology also has a significant effect on the performance of MSMEs in Banjarmasin, with a Sig value of 0.006. The F value is 8.355 with a significance of 0.001, it is concluded that Entrepreneurial Orientation (X1) and Information Technology (X2) have a significant influence on the performance of MSMEs. The combined influence of Entrepreneurial Orientation and Information Technology as shown by an R-Square value of 0.188 or 18.8% indicates the existence of interdependence.